Performance analysis of rolling bearing in conveyor belt idlers - Borges, Bruna Kolczycki (2019)
Nowadays, energy saving and environmental awareness are global requirements for creating a sustainable society. Rolling bearings need to transmit load at a very low friction, therefore understanding internal friction losses in these elements is relevant for energy saving. Specifically for idler rolls of conveyor belts, rolling bearings represent one of the main sources of idler failure and power loss. Based on conveyor belt design it is possible to properly define operating conditions of rolling bearings and then use friction torque models to predict the idler’s rolling resistance needed to overcome frictional resistance on its bearings. Conveyor belt bearings are grease lubricated, their lubrication mechanisms are not yet well understood and there is no consensus on the correlation between grease properties and its performance. With the significant number of models aiming to predict film thickness and friction torque, few are valid for grease lubrication and the ones that are only consider base oil properties. Rheological measurements show the need to use grease apparent viscosity instead of base oil viscosity depending on the bearing operation conditions. This difference in viscosity promotes a significant difference in friction torque predictions and consequently, energy consumption.